Pemberdayaan Ibu-Ibu PKK dan Kader Posyandu RW 022 Teluk Pucung, Bekasi Utara dalam Penerapan Gema Cermat (Gerakan Masyarakat Cerdas Menggunakan Obat) - Elly Wardani; Rizky Arcinthya Rachmania (Jurnal Pengabdian Pada Masyarakat, 2020)
EMPOWERMENT OF PKK WOMEN AND POSYANDU CADRE OF RW 022 TELUK PUCUNG, NORTH BEKASI IN THE APPLICATION OF GEMA CERMAT (INTELLIGENT COMMUNITIES USING MEDICINE). Until now in the midst of society often encountered various problems in the use of drugs, including lack of understanding of the use of appropriate and rational drugs, excessive use of over-the-counter drugs, and a lack of understanding of how to store and dispose of drugs properly. While health workers are still perceived as lacking adequate information about drug use. This is based on the appropriateness of data and information sources collected through visits and good discussions with several representatives of PKK women members and Posyandu Cadres RW 22 Teluk Pucung, North Bekasi. There are still many found, especially North Bekasi residents who sell or exchange used drugs to collectors of used goods in their residential areas or there are still many people who store liquid preparations such as syrup in the refrigerator. The purpose of this activity is to increase understanding of the treatment of drugs in how to get, use, store and dispose of and increase the rational use of drugs through Gema Cermat. The method of activities to solve the problems faced by PKK women and Posyandu cadres is by socializing about the Gema Cermat by filling out the questionnaire before and after the socialization. Based on the results of the pre-test and post-test questionnaires, the participants became more aware of the management of drugs at home and increased knowledge of the use of rational drugs such as antibiotics. The conclusion of this activity is to increase participants’ understanding of drug management properly and is expected to be implemented in the family and community environment.